PENINGKATAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PKN MENGGUNAKAN MEDIA AUDIOVISUAL KELAS IV - Apriyanti, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to obtain information that is clearly on Improving Students' Motivation in Learning PKn Using Audiovisual Media in Class IVB SDN 20 Pontianak Selatan. This research uses descriptive method. Form of classroom action research collaborative. Data collection technique used is the technique of direct observation by observation sheet data collection tool. Setting research in class IVB the number of students as many as 36 people. This research was conducted as many as two cycles with the results obtained, ability of teachers plan learning in cycle I is 3,45. In the second cycle increased to 3,85. The average ability of teachers in implementing the learning in cycle I is 3,20. In the second cycle increased to 3,80. And for the students' motivation in the first cycle average is 65,04% and the second cycle increased to 77,54%. This proves that the application of the audiovisual media in PKn learning can increase learning motivation IVB grade students of SDN 20 Pontianak Selatan. Keyword: Learning Motivation, Audiovisual Media.